Pengalaman Intersubyektif Remote Audit: Masa Covid dan Post Covid - Risyad Alfiqho Martha; M. Nur Abdullah Birton; M. Adrian Muluk (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2025)
Main Purpose - to explain interactions (intersubjective) between individual auditors and between auditors and auditees in implementing remote both during pandemic and after the COVID-19 pandemic Method - This research applies a qualitative approach with In-depth interviews. Using Alfred Schutz's intersubjective phenomenology and combined with Interpretative Phenomenological Analysis (IPA) to analyze the data. Main Findings - During the COVID-19 pandemic, intersubjectivity is unavoidable in the daily experiences of each individual auditor and auditee. Even though there are government policies related to social finance, interaction between auditors and auditees is still maintained by implementing alternative remote audit procedures. Meanwhile, interactions between individual auditors occur directly due to the policies of the leadership of the public accounting firm. After the COVID-19 pandemic, the use of hybrid methods resulted in the intensity of direct interaction between audit teams reducing reductions in the planning and implementation stages. Theory and Practical Implications - The effective use of remote audits during the pandemic and post-pandemic has implications for making audit data collection easier, auditors can focus more on examining material accounts and shorten audit time in meeting audit deadlines. Novelty - This study presents a novelty in terms of the data analysis method used, namely Interpretative Phenomenological Analysis (IPA) on this topic.